ANALISIS PERAN UMKM SEBAGAI PONDASI KEMASLAHATAN PEREKONOMIAN MASYARAKAT INDONESIA DI MASA PANDEMI COVID-19 - Rina Desiana; Cut Dian Fitri; Muhammad Rival Hasibuan; Awang Darmawan Putra (Politeknik Bisnis Indonesia, 2021)
Micro, Small, and Medium Enterprises (MSMEs) are one of the pillars and contribute to the Indonesian economy. One of the factors contributing to the decline in MSMEs is the result of the Covid-19 pandemic. This study aims to determine the role of MSMEs as the foundation for the economic benefit of the Indonesian people during the Covid-19 pandemic and the obstacles in the development of MSMEs. This type of research is a qualitative research that is literature review or library research by using library data obtained from various sources of library information related to research such as through abstracts of research results, indexes, reviews, journals, and reference books. This study refers to the results of research from the Indonesian Institute of Sciences (LIPI) entitled